The legal nature of nullity in a period of suspicion - شاكر رشا كيلان (Journal of Legal Sciences, 2020)
Represents the period of suspicion period between start date stop payment and date of issuance of the rule of bankruptcy, and that behavior performed by the merchant debtor in this period is the behaviors suspicious. Once to stop the merchant debtor to pay its debts makes his action marred by disorder. as it may harm creditors or a preference for each of other because it feels along of bankruptcy or it may oversaw so distrust legislator of his action in this period which is the most dangerous periods and most dangerous on creditors , the legislator stipulated that action issued by the debtor during this period should be null void the aim of the legislator is to protect the creditor community and that the non-exhaustion of the disposition of the period of suspicion is more comprehensive and easier than that prescribed for creditors in the general rules of the right to request that the disposition of the action not be disposed of by police action . therefore, it was necessary to state the nature of the nullity and determine the period of suspicion and then address the deadlock and the absence of the conditions and behaviors subject to both types of nullity.